A Spatial Tropical Island Database of Northern Borneo, Malaysia using Google Earth - Mohd Harun Abdullah; Zulherry Isnain; Kam-Cheng Yeong; Thor-Seng Liew; Mohd. Talha Anees; Lin, Chin Yik (Malaysian Journal of Science (MJS), 2024)
The state of Sabah in Northern Borneo, Malaysia is surrounded by numerous small tropical islands. However, the recent surge in tourist activities has significantly impacted the biological diversity and natural resources of these islands. This study aims to develop a systematic database for the region prioritize and preserved the conservation and integrity of these tropical islands. The database was compiled using topographic maps and Google Earth data. Variables such as island size, distance, distribution, and isolation from the Sabah coastline were analysed through maps and scatter plots generated in a GIS environment. The significance of the islands was evaluated across various aspects based on the compiled data. The database identifies a total of 510 islands along Sabah’s coastline with 82 located on the west coast and the remaining 428 on the east coast. Approximately 80% of these islands are small with an area of less than 1 km2. Only five islands exceed 100 km2, while smaller islands are predominantly located closer to the coast. The finding indicate that the significance of the islands varies based on factors such as tourist attractions, flora and fauna, marine ecosystems, and national security. The methodology adopted in this study is robust and offers potential for examining island distribution in other regions.